2012
DOI: 10.1103/physrevc.86.024911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of initial flow velocity fluctuation in event-by-event (3+1)D hydrodynamics

Abstract: Hadron spectra and elliptic flow in high-energy heavy-ion collisions are studied within a (3+1)D ideal hydrodynamic model with fluctuating initial conditions given by the AMPT Monte Carlo model. Results from event-by-event simulations are compared with experimental data at both RHIC and LHC energies. Fluctuations in the initial energy density come from not only the number of coherent soft interactions of overlapping nucleons but also incoherent semi-hard parton scatterings in each binary nucleon collision. Min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
204
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(206 citation statements)
references
References 155 publications
(187 reference statements)
1
204
0
1
Order By: Relevance
“…In particular, it was recently observed that azimuthal correlations decrease as a function of the relative pseudorapidity [42], at variance with common lore that correlations due to flow are essentially independent of rapidity. While standard models of initial conditions do predict a mild rapidity dependence of azimuthal correlations [43,44], longitudinal fluctuations [45] could also produce a decoherence effect similar to the one studied here. The detailed structure of two-particle correlations as a function of both particle momenta thus opens a new window on the study of flow fluctuations.…”
Section: Discussionmentioning
confidence: 87%
“…In particular, it was recently observed that azimuthal correlations decrease as a function of the relative pseudorapidity [42], at variance with common lore that correlations due to flow are essentially independent of rapidity. While standard models of initial conditions do predict a mild rapidity dependence of azimuthal correlations [43,44], longitudinal fluctuations [45] could also produce a decoherence effect similar to the one studied here. The detailed structure of two-particle correlations as a function of both particle momenta thus opens a new window on the study of flow fluctuations.…”
Section: Discussionmentioning
confidence: 87%
“…The properties of the QGP, in particular its shear viscosity, can be deduced by studying its efficiency of converting initial geometric anisotropies into final anisotropic flows. Because of this, measurements of collective flow anisotropies v n (initially the elliptic flow v 2 , more recently higher-order harmonic flows v n≥3 [22][23][24][25][26][27]) have generated strong interest and fertilized the study of initial geometry fluctuations and their dynamical consequences [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical calculations by Bozek et al [150], Petersen et al [151] and Pang et al [111] demonstrate that longitudinal fluctuations may result in non-trival pseudorapidity dependencies of the triangular flow event plane and two-particle correlations. In some calculations, one can even find that the v 3 flow vector is anticorrelated between the far forward and backward regions [152].…”
Section: Longitudinal Fluctuationsmentioning
confidence: 99%
“…Transport approaches like NEXUS [103,79], EPOS [72,104,105], UrQMD [106,71,107,108,109,110] and AMPT [111] have been used to provide initial conditions for hybrid models. Employing a dynamical approach to generate an initial condition for the hydrodynamic evolution allows for a treatment of the non-equilibrium dynamics.…”
Section: Dynamic Approachesmentioning
confidence: 99%